RENCANA BISNIS PENGEMBANGAN USAHA PENGOLAHAN METE (Anancardium occidentalle L) DI SUBAK ABIAN DHARMA SANTI, DESA DATAH - KARANGASEM - Punia Atmaja, I Kadek; Satriawan, I Ketut; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 3 (2015): September, 2015)
The purpose of this study is to formulate business development strategy of cashew processing in Subak Abian Dharma Santi, Datah village, Karangasem and determine the feasibility of developing a business plan cashew processing business in terms of aspects of feasibility. This study used a SWOT analysis to formulate strategy and to determine the feasibility of business plan enterprise development cashew processing analysis of market and marketing aspects, technical and technological aspects, management and human resources aspects, and financial aspects with the eligibility criteria such as NPV, IRR, B / CR, and PBP. Business plan enterprise development position in Subak Abian Dharma Santi based matrix position is in quadrant II, which means that in spite of all external threats. Business development of the cashew processing in Subak Abian Dharma Santi has the advantage of resources, and alternative strategies produced are: (1) conducting promotional products processing cashew ready for consumption intensive and efficient, (2) producing cashew ready for consumption with good quality so as to compete in the market. Analysis of the feasibility study financial aspects of the business plan enterprise development, cashew processing in Subak Abian Dharma Santi viable seen from NPV of Rp 83.988.304, IRR of 26,55%, B / CR at 1.24, and PBP 3 year 1 months. Keywords: business plan, strategy, subak abian, cashew
Keywords: 55